Beyond reducing direct medical cost: examining health outcomes in tuberculosis through a difference-in-differences analysis of South Korea’s out-of-pocket payment exception policy - Yu, Sarah; Moon, Daseul; Jeong, Dawoon; Kang, Young Ae; Lee, Gyeong In; Choi, Hongjo (Frontiers in Public Health, 2024)
Background Universal health coverage and social protection are major global goals for tuberculosis. This study aimed to investigate the effects of an expanded policy to guarantee out-of-pocket costs on the treatment outcomes of patients with tuberculosis. Methods By linking the national tuberculosis report and health insurance data and performing covariate-adjusted propensity-score matching, we constructed data on health insurance beneficiaries (treatment group) who benefited from the out-of-pocket payment exemption policy and medical aid beneficiaries as the control group. Using difference-in-differences analysis, we analyzed tuberculosis treatment completion rates and mortality in the treatment and control groups. Results A total of 41,219 persons (10,305 and 30,914 medical aid and health insurance beneficiaries, respectively) were included in the final analysis (men 59.6%, women 40.4%). Following the implementation of out-of-pocket payment exemption policy, treatment completion rates increased in both the treatment and control groups; however, there was no significant difference between the groups (coefficient, −0.01; standard error, 0.01). After the policy change, the difference in mortality between the groups increased, with mortality decreasing by approximately 3% more in the treatment group compared with in the control group (coefficient: −0.03, standard error, 0.01). Conclusion There are limitations to improving treatment outcomes for tuberculosis with an out-of-pocket payment exemption policy alone. To improve treatment outcomes for tuberculosis and protect patients from financial distress due to the loss of income during treatment, it is essential to proactively implement complementary social protection policies.